2018
DOI: 10.1249/mss.0000000000001543
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Strength Training on Postpubertal Adolescent Distance Runners

Abstract: Ten weeks of strength training added to the program of a postpubertal distance runner was highly likely to improve maximal speed and enhances RE by a small extent, without deleterious effects on body composition or other aerobic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…Three studies have investigated the effect of ST specifically in young (<18 years) middle-or long- running test and 30 m sprint) compared to a running-only group. It is noteworthy that both of these investigations (17,58) included sprints (3-10 x 30-150 m) as part of the intervention, which provides a highly specific overload to the neuromuscular system in endurance runners. Interestingly, participants in the ST intervention groups in these studies reduced their weekly running volume to accommodate the additional S&C activities.…”
Section: Efficacy In Adolescent Runnersmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies have investigated the effect of ST specifically in young (<18 years) middle-or long- running test and 30 m sprint) compared to a running-only group. It is noteworthy that both of these investigations (17,58) included sprints (3-10 x 30-150 m) as part of the intervention, which provides a highly specific overload to the neuromuscular system in endurance runners. Interestingly, participants in the ST intervention groups in these studies reduced their weekly running volume to accommodate the additional S&C activities.…”
Section: Efficacy In Adolescent Runnersmentioning
confidence: 99%
“…Each training unit takes 10-20 min to complete, thus making it easy to integrate some purposeful S&C prior to or after running sessions. It is important to note that studies in adolescent distance runners (17,58) have shown that including weekly ST sessions are more effective than increasing running volume, at least in the short-term (8-10 weeks).…”
Section: Organization Of the Training Microcyclementioning
confidence: 99%
See 3 more Smart Citations